Biodiversity gill fish parasites from gulf of Bejaia, Algerian waters - RAMDANI, Souhila (Archives of Veterinary Science, 2025)
The gills of 12 species of commercial fishes were examined for their parasites on the Gulf of Bejaia, Algeria. Divers parasites were identified among these gill hosts. nine crustacean: Clavella adunca, Lernaea sp., Clavellisa emarginata, Naobranchia cygniformis, Hatschekia mulli, Lernanthropus kroyeri, Caligus elongatus, Gnathia marleyi, and Caligus sp. Six monogenean: Bivagina pagrosomi, Rajonchocotyle batis, Microcotyle erythrini, Squalonchocotyle squali, Paradiplozoon sp., and Tristoma integrum. One Hirudinea, Trachelobdella lubrica. Several unidentified parasite forms, were also collected. We provide in this study a new locality record, from Algerian sea for species Rajonchocotyle batis, Squalonchocotyle squali, Caligus elongatus. Moreover, this paper presents new host and locality record for species Bivagina Pagrosomi infecting Trachurus trachurus and Paradiplozoon sp. infecting Boops boops and Gnathia marleyi infecting Sparus aurata. Keywords: fish, gills, parasites, biodiversity, Bejaia, Algeria.